Systemic Lupus Erythematosus and Systemic Autoimmune Connective Tissue Disorders behind Recurrent Diastolic Heart Failure - Luis Miguel Blasco Mata; Olga Acha Salazar; Carmen Rosa González-Fernández; Francisco Novo Robledo; Enrique Pérez-Llantada Amunárriz (Clinical and Developmental Immunology)
Diastolic heart failure (DHF) remains unexplained in some patients with recurrent admissions after full investigation. A study was directed for screening SLE and systemic autoimmune connective tissue disorders in recurrent unexplained DHF patients admitted at a short-stay and intermediate care unit. It was found that systemic autoimmune conditions explained 11% from all of cases. Therapy also prevented new readmissions. Autoimmunity should be investigated in DHF.